Fractional order operational matrix methods for fractional singular integro-differential equation - Singh C.S.; Singh H.; Singh V.K.; Singh O.P. (My University, 2025)
In this paper, we obtain the numerical method for the fractional order singular Volterra integro-differential equations which are typical for the theory of Brownian motion based on the fractional Langevin equation and Basset force. The proposed method is based on the fractional order operational matrices of integration and differentiation of the Legendre scaling function. © 2016 Elsevier Inc.